PLANKTONIC DIVERSITY OF FRESH-WATER BODIES IN ALLPAHUAYO MISHANA NATIONAL RESERVE, LORETO – PERU - CHÁVEZ-VEINTEMILLA, Carlos (2021)
The objective of this study was to determine the existing planktonic diversity in the different water bodies of the Allpahuayo Mishana National Reserve, Loreto Peru. The research was conducted in 16 stations located in lotic and lentic water bodies. The collection, identification and analysis of biological communities was carried out using the MINAM & UNMSM (2014) methodology and the Shannon-Weaver, Margaleff, Simpson and Pielou indices were measured using the PAST program. We found 39 species of phytoplankton in the wet season, whose dominant taxa were Bacillariophyta, Charophyta, Chlorophyta and Euglenozoa, while in the dry season 63 species were identified, whose dominant taxa were Bacillariophyta, Charophyta, Chlorophyta and Cyanobacteria. For the zooplankton in the humid season, 17 species were identified and in the dry season 24 species and coincidentally they were dominated by the taxa Rotatoria, Protozoa and Arthropoda. The Shannon-Weaver indices showed an average or normal biodiversity; Margaleff that diversity was related to the richness and abundance of their environments, Simpson that in general there is no dominance of a particular species, and Pielou that there are communities in balance. We conclude that the waters of the middle basin of the Nanay River and Allpahuayo Mishana National Reserve are still healthy, despite the impact that occurs around it.